(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of Uzbekistan’s rich abundance of mineral and raw resources, highlighting its significance in the country’s economy.It emphasizes Uzbekistan’s substantial gold reserves and its position as one of the world’s largest producers of gold. It discusses the Muruntau Gold Mine as one of the largest open-pit gold mines globally, contributing significantly to the country’s economy.Copper describes Uzbekistan’s significant reserves of copper and the role of the Almalyk mining and metallurgical combine as the main producer of copper in the country.Highlights the importance of copper mining in providing employment and contributing to the country’s GDP.Also it highlights the Navoi Mining and Metallurgy Combinat as the country’s largest uranium producer, with substantial processing capacity.